Comparative Transcriptome Analysis Revealed Candidate Genes Potentially Related to Desiccation Sensitivity of Recalcitrant Quercus variabilis Seeds - Li, Dongxing; Li, Yingchao; Qian, Jialian; Liu, Xiaojuan; Xu, Huihui; Zhang, Guowei; Ren, Junjie; Wang, Libing; Zhang, Lu; Yu, Haiyan (Frontiers in Plant Science, 2021)
Chinese cork oak (Quercus variabilis) is a widely distributed and highly valuable deciduous broadleaf tree from both ecological and economic perspectives. Seeds of this species are recalcitrant, i.e., sensitive to desiccation, which affects their storage and long-term preservation of germplasm. However, little is known about the underlying molecular mechanism of desiccation sensitivity of Q. variabilis seeds. In this study, the seeds were desiccated with silica gel for certain days as different treatments from 0 day (Control) to 15 days (T15) with a gradient of one day. According to the seed germination percentage, four key stages (Control, T2, T4 and T11) were found. Then the transcriptomic profiles of these four stages were compared. A total of 4405, 4441, and 5907 differentially expressed genes (DEGs) were identified in T2 vs Control, T4 vs Control, and T11 vs Control, respectively. Among them, 2219 DEGs were overlapped in the three comparison groups. Kyoto Encyclopaedia of Genes and Genomes (KEGG) enrichment analysis showed that these DEGs were enriched into 124 pathways, such as "Plant hormone signal transduction" and "Glycerophospholipid metabolism". DEGs related to hormone biosynthesis and signal transduction (ZEP, YUC, PYR, ABI5, ERF1B, etc.), stress response proteins (LEA D-29, HSP70, etc.), and phospholipase D (PLD1) were detected during desiccation. These genes and their interactions may determine the desiccation sensitivity of seeds. In addition, we also identified group specific DEGs in T2 vs Control (PP2C62, UNE12, etc.), T4 vs Control (WRKY1-like, WAK10, etc.) and T11 vs Control (IBH1, bZIP44, etc.), respectively. Finally, a possible work model was proposed to show the molecular regulation mechanism of desiccation sensitivity in Q. variabilis seeds. This is the first report on the molecular regulation mechanism of desiccation sensitivity of Q. variabilis seeds using RNA-Seq. Our findings could make a great contribution to seed storage and long-term conservation of recalcitrant seeds in the future.